2015
DOI: 10.1016/j.enbuild.2014.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Using BEopt (EnergyPlus) with energy audits and surveys to predict actual residential energy usage

Abstract: Simulations of building energy use can give insights into how energy efficiency retrofits and operational changes can influence a building's total and temporal energy use. However, before those models are used to generate recommendations, it is important to understand how accurately the simulations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…Results of this paper show that the average actual energy use varied by 5-7% of the predicted energy use, but at individual buildings level the deviation could be as high as 60% higher or lower. Large variations were also found in previous studies [7][8][9][10][11][13][14][15][16][17][18][19], which shows that it is difficult to choose an appropriate safety factor in energy use predictions. However, more data on actual energy use would help deduce realistic input data to be used in energy simulation models.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Results of this paper show that the average actual energy use varied by 5-7% of the predicted energy use, but at individual buildings level the deviation could be as high as 60% higher or lower. Large variations were also found in previous studies [7][8][9][10][11][13][14][15][16][17][18][19], which shows that it is difficult to choose an appropriate safety factor in energy use predictions. However, more data on actual energy use would help deduce realistic input data to be used in energy simulation models.…”
Section: Discussionsupporting
confidence: 58%
“…Branco et al [9] reported that actual energy use of low-energy multi-family buildings in Switzerland was 50% higher than predicted. Rhodes et al [10] found that the actual energy of individual single-family houses in Austin, USA could vary by 28% of the predicted energy use. A German study reported that the measured energy use was on average 30% lower than the predicted use [11].…”
Section: Objectivesmentioning
confidence: 99%
“…The output taken from the model is the total building cooling load (the amount of thermal energy that is removed from the space) for every hour time interval, which is then fed into the air conditioning and TES system model. Benchmarking BEopt with measured home electricity data has shown that while individual comparisons of energy use can differ significantly (both higher and lower), on average the modeling is reasonably accurate (within approximately 3%) at estimating electricity use [53].…”
Section: Modeling the House Thermal Loadmentioning
confidence: 97%
“…Simulations of building energy use can give insights into how energy efficiency retrofits and operational changes can influence a building's total and temporal energy use [20]. Rhodes et al [21] determined model accuracy by considering 54 homes in Austin, TX, that are part of a smart grid demonstration project. Lee et al [22] investigated retrofit tools both in the public domain as well as in the private sector to better understand the diverse approaches currently in use to evaluate retrofit methods, measures, interoperability, target audiences, as well as interface types and accessibility.…”
Section: Building Energy Retrofit In Hot-humid Climatementioning
confidence: 99%